An experimental study on the effectiveness of disclosing stressful life events and support messages: when cognitive reappraisal support decreases emotional distress, and emotional support is like saying nothing at all. - Anika Batenburg; Enny Das (PLoS ONE, 2014)
How can we best support others in difficult times? Studies testing the effects of supportive communication revealed mixed findings. The current study focuses on the effects of supportive communication following different disclosure styles, and includes outcome measures to assess emotional well-being. Hypotheses were tested in a 2 (disclosure style: cognitive reappraisal disclosure vs. emotional disclosure) × 3 (support message: cognitive reappraisal response vs. socio-affective response vs. no response) between subjects factorial design. Receiving a cognitive reappraisal response, rather than a socio-affective response or no response, decreased emotional distress in the emotional disclosure group. Support messages showed no effects in the cognitive reappraisal disclosure group. Although socio-affective responses were positively evaluated, cognitive reappraisal responses may be more effective during emotional upheaval because they provide a positive way out of negative emotions.